Development Of Interactive Media For English Learning - Wawan Gunawan; Atiqoh Atiqoh; Yoso Wiyarno; Suharti Suharti; Imas Mastoah (Journal on Education, 2023)
The purpose of this development is to produce an English Language Learning Interactive Media. The selection of this model is based on the consideration that this model is easy to understand, developed systematically, and is based on the theoretical foundation of the developed learning design. The development process involves (1) learning design experts (2) content experts in the field of study (3) small group trials to provide feedback and input for improvements. The results of this development research are that this interactive media product has a material feasibility level of 90%, learning design feasibility is 94% and small group trials are 90% with very decent qualifications and does not need to be revised. Based on the results of this study, it was concluded that using Interactive Learning Media can improve English learning outcomes. The implication of this research is that Learning Interactive Media can be used as a way to improve English learning outcomes.